The SDF-1α/CXCR4 Axis is Required for Proliferation and Maturation of Human Fetal Pancreatic Endocrine Progenitor Cells - Kayali, Ayse G.; Lopez, Ana D.; Hao, Ergeng; Hinton, Andrew; Hayek, Alberto; King, Charles C. (PLOS ONE, 2012)
The chemokine receptor CXCR4 and ligand SDF-1α are expressed in fetal and adult mouse islets. Neutralization of CXCR4 has previously been shown to diminish ductal cell proliferation and increase apoptosis in the IFNγ transgenic mouse model in which the adult mouse pancreas displays islet regeneration. Here, we demonstrate that CXCR4 and SDF-1α are expressed in the human fetal pancreas and that during early gestation, CXCR4 colocalizes with neurogenin 3 (ngn3), a key transcription factor for endocrine specification in the pancreas. Treatment of islet like clusters (ICCs) derived from human fetal pancreas with SDF-1α resulted in increased proliferation of epithelial cells in ICCs without a concomitant increase in total insulin expression. Exposure of ICCs in vitro to AMD3100, a pharmacological inhibitor of CXCR4, did not alter expression of endocrine hormones insulin and glucagon, or the pancreatic endocrine transcription factors PDX1, Nkx6.1, Ngn3 and PAX4. However, a strong inhibition of β cell genesis was observed when in vitro AMD3100 treatment of ICCs was followed by two weeks of in vivo treatment with AMD3100 after ICC transplantation into mice. Analysis of the grafts for human C-peptide found that inhibition of CXCR4 activity profoundly inhibits islet development. Subsequently, a model pancreatic epithelial cell system (CFPAC-1) was employed to study the signals that regulate proliferation and apoptosis by the SDF-1α/CXCR4 axis. From a selected panel of inhibitors tested, both the PI 3-kinase and MAPK pathways were identified as critical regulators of CFPAC-1 proliferation. SDF-1α stimulated Akt phosphorylation, but failed to increase phosphorylation of Erk above the high basal levels observed. Taken together, these results indicate that SDF-1α/CXCR4 axis plays a critical regulatory role in the genesis of human islets.